دورأخلاقيات العمل في تعزيز المسؤولية الاجتماعية في مؤسسة خدمية دراسة حالة مديرية المصالح الفلاحية لولاية سوق أهراس - - عبد النور قدادرية; محمد عبد المالك زيد (My University, 2022)
This study aims to try to identify both business ethics and social responsibility. And it all aims to study the relationship between them through a case study of a service institution represented in the Directorate of Agricultural Interests in the state of Souk Ahras. It was use through the questionnaire as a tool for collecting information in the field study and using the SPSS program to process the data collected from the study sample. The study was concluded that business ethics contribute to enhancing social responsibility by adopting this type of institution for its economic, legal, moral and good dimensions, and a relationship between the study variables. ......................................................... تهدف هذه الدراسة إلى محاولة التعرف على كل من أخلاقيات الأعمال والمسؤولية الاجتماعية ودراسة العلاقة بينهما من خلال دراسة حالة لمؤسسة خدمية تتمثل في مديرية المصالح الفلاحية لولاية سوق أهراس عن طريق الاستبيان كأداة لجمع البيانات في الدراسة الميدانية و من ثم استخدام برنامج SPSS لمعالجة المعطيات المجمعة من عينة الدراسة. وتوصلت الدراسة إلى أن أخلاقيات الأعمال تساهم في تعزيز المسؤولية الاجتماعية من خلال تبني هذا النوع من المؤسسات لأبعاد المسؤولية الاجتماعية : الاقتصادية والقانونية والأخلاقية والبعد الخيري، و وجود علاقة تكامل بين متغيرات الدراسة.